2014
DOI: 10.1063/1.4895614
|View full text |Cite
|
Sign up to set email alerts
|

A new feature in the internal heavy isotope distribution in ozone

Abstract: Ozone produced by discharge or photolysis of oxygen has unusually heavy isotopic composition ((18)O/(16)O and (17)O/(16)O ratio) which does not follow normal mass fractionation rule: δ(17)O ∼ 0.52(*)δ(18)O, expressed as an anomaly Δ(17)O = δ(17)O - 0.52(*)δ(18)O. Ozone molecule being an open isosceles triangle can have the heavy isotope located either in its apex or symmetric (s) position or the base or asymmetric (as) position. Correspondingly, one can define positional isotopic enrichment, written as δ(18)O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Previous modeling studies showed good agreement with observations of 17 O(nitrate) when assuming that the bulk oxygen isotopic composition of ozone ( 17 O(O 3 )) is equal to 35 ‰ (Alexander et al, 2009;Michalski et al, 2003) but varied in their assumption on terminal oxygen atom versus statistical isotopic transfer from O 3 to the reactant (NO and NO 2 ). This is an important distinction because it is now known that the 17 O enrichment in O 3 is contained entirely in its terminal oxygen atoms, and it is the terminal oxygen atom that is transferred from O 3 Berhanu et al, 2012;Bhattacharya et al, 2008Bhattacharya et al, , 2014Savarino et al, 2008;Michalski and Bhattacharya, 2009), so that the 17 O value of the oxygen atom transferred from ozone to the product is 50 % larger than the bulk 17 O(O 3 ) value. Recently, much more extensive observations of 17 O(O 3 ) using a new technique (Vicars et al, 2012) consistently show 17 O(O 3 ) = 26±1 ‰ in diverse locations (Vicars et al, 2012;Ishino et al, 2017;Vicars and Savarino, 2014) and suggest that previous modeling studies are biased low in 17 O(nitrate) (e.g., Alexander et al 2009), which would occur if the model underestimated the relative role of ozone in NO x chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Previous modeling studies showed good agreement with observations of 17 O(nitrate) when assuming that the bulk oxygen isotopic composition of ozone ( 17 O(O 3 )) is equal to 35 ‰ (Alexander et al, 2009;Michalski et al, 2003) but varied in their assumption on terminal oxygen atom versus statistical isotopic transfer from O 3 to the reactant (NO and NO 2 ). This is an important distinction because it is now known that the 17 O enrichment in O 3 is contained entirely in its terminal oxygen atoms, and it is the terminal oxygen atom that is transferred from O 3 Berhanu et al, 2012;Bhattacharya et al, 2008Bhattacharya et al, , 2014Savarino et al, 2008;Michalski and Bhattacharya, 2009), so that the 17 O value of the oxygen atom transferred from ozone to the product is 50 % larger than the bulk 17 O(O 3 ) value. Recently, much more extensive observations of 17 O(O 3 ) using a new technique (Vicars et al, 2012) consistently show 17 O(O 3 ) = 26±1 ‰ in diverse locations (Vicars et al, 2012;Ishino et al, 2017;Vicars and Savarino, 2014) and suggest that previous modeling studies are biased low in 17 O(nitrate) (e.g., Alexander et al 2009), which would occur if the model underestimated the relative role of ozone in NO x chemistry.…”
Section: Introductionmentioning
confidence: 99%